Ibrutinib, lenalidomide and dexamethasone in patients with relapsed and/or refractory multiple myeloma: Phase I trial results. Issue 4 (8th May 2022) - Ailawadhi, Sikander; Parrondo, Ricardo D.; Moustafa, Muhamad Alhaj; LaPlant, Betsy R.; Alegria, Victoria; Chapin, Dustin; Roy, Vivek; Sher, Taimur; Paulus, Aneel; Chanan‐Khan, Asher A.
Abstract: Therapeutic strategies that target novel pathways are urgently needed for patients with relapsed/refractory multiple myeloma (RRMM). Ibrutinib is an oral covalent inhibitor of Bruton tyrosine kinase, which is overexpressed in MM cells. This phase 1 dose‐escalation study examined various doses of ibrutinib in combination with standard doses of lenalidomide (25 mg) and dexamethasone (40 mg) using a standard 3 + 3 design in RRMM patients. The primary objective was to determine the maximum tolerated dose (MTD) of ibrutinib in combination with lenalidomide and dexamethasone. Patients ( n = 15) had received a median of 4 prior regimens, 53% were triple‐class exposed, 33% were penta‐exposed, and 54% were lenalidomide‐refractory. The MTD of ibrutinib was 840 mg ( n = 6) and only 1 dose‐limiting toxicity; a grade 3 rash possibly related to ibrutinib was noted. The most common ≥ grade 3 adverse events were rash in 2 (13%), lymphopenia in 2 (13%), leukopenia, neutropenia, thrombocytopenia, and anemia all occurring in 3 (20%) patients each. One patient achieved a partial response for an overall response rate of 7%. The clinical benefit rate was 80%. The median time to progression was 3.8 months. Ibrutinib, lenalidomide and dexamethasone appears to be a safe and well‐tolerated regimen with reasonable efficacy in heavily pretreated RRMM patients.